Practical Path to Empower the Intelligence of Moral and Legal Education Resources - Wu, Jiaqi; Qu, Zhangyan (Innovative Applications of AI, 2025)
This article focuses on artificial intelligence to empower the intelligent application of moral and legal education resources, and explores its important role, real challenges and practical paths. Artificial intelligence can promote the "intelligent integration", "dynamic update" and "precise push" of moral and legal education resources, and improve the aggregation, timeliness and adaptability of moral and legal education resources, but face problems such as data processing and resource complexity adaptation difficulties, obstacles to teacher technology integration, and contradictions in student learning needs and resource utilization. To meet these challenges, we can promote the high-quality development of moral and legal education and realize the internalization and practice of moral and legal education results by strengthening the compatibility of artificial intelligence with moral and legal education resources, enhancing teachers' artificial intelligence literacy, and stimulating students' participation.